End-Stage Renal Disease Causes Skewing in the TCR Vβ-Repertoire Primarily within CD8+ T Cell Subsets - Huang, Ling; Betjes, Michiel G. H.; Klepper, Mariska; Langerak, Anton W.; Baan, Carla C.; Litjens, Nicolle H. R. (Frontiers in Immunology, 2017)
A broad T cell receptor (TCR-) repertoire is required for an effective immune response. TCR-repertoire diversity declines with age. End-stage renal disease (ESRD) patients have a prematurely aged T cell system which is associated with defective T cell- mediated immunity. Recently, we showed that ESRD may significantly skew the TCR Vb-repertoire. Here we assessed the impact of ESRD on the TCR Vb-repertoire within different T cell subsets using a multi-parameter flow-cytometry-based assay, controlling for effects of ageing and CMV latency. Percentages of 24 different TCR Vb-families were tested in circulating naïve and memory T cell subsets of 10 ESRD patients and 10 age- and CMV-serostatus-matched healthy individuals (HI). The Gini-index, a parameter used in economics to describe the distribution of income, was calculated to determine the extent of skewing at the subset level taking into account frequencies of all 24 TCR Vb-families. In addition, using HI as reference population, the differential impact of ESRD was assessed on clonal expansion at the level of an individual TCR Vb-family. CD8+, but not CD4+, T cell differentiation was associated with higher Gini-TCR indices. Gini-TCR indices were already significantly higher for different CD8+ memory T cell subsets of younger ESRD patients compared to their age-matched HI. ESRD induced expansions of not one TCR Vb-family in particular and expansions were predominantly observed within the CD8+ T cell compartment. All ESRD patients had expanded TCR Vb-families within total CD8+ T cells and the median (IQ range) number of expanded TCR Vb-families/patient amounted to 2 (1-4). Interestingly, ESRD also induced clonal expansions of TCR Vb-families within naïve CD8+ T cells as 8 out of 10 patients had expanded TCR Vb-families. The median (IQ range) number of expanded families/patient amounted to 1 (1-1) within naïve CD8+ T cells. In conclusion, loss of renal function skews the TCR Vb-repertoire already in younger patients by inducing expansions of different TCR Vb-families within the various T cell subsets, primarily affecting the CD8+ T cell compartment. This skewed TCR Vb-repertoire may be associated with a less broad and diverse T cell-mediated immunity.